2017
DOI: 10.1177/1098612x17730707
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of the caudal fossa of domestic cat skulls assessed with CT and geometric morphometrics analysis

Abstract: Objectives This study aimed to investigate differences and demonstrate a normal range of morphological variation of the caudal fossa of the cranium of domestic cats. Methods CT scans of 32 domestic cat heads of 11 breeds were included. Isosurfaces from skulls were characterised through three-dimensional geometric morphometrics using geographical landmarks placed on the internal surface of the caudal fossa and foramen magnum. Raw data was transformed with a Procrustes fit and coordinate covariance was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Also, the skull indices obtained from these cranial measurements are quite effective in distinguishing or identifying morphological types (21). For this reason, various craniometric measurements have been used in the studies in determining the morphological variations between the domestic and wild cat species (6,8,14,30,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the skull indices obtained from these cranial measurements are quite effective in distinguishing or identifying morphological types (21). For this reason, various craniometric measurements have been used in the studies in determining the morphological variations between the domestic and wild cat species (6,8,14,30,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements obtained from skull using computed tomography (CT) and three -dimensional modelling software may be mostly used in revealing the biometric differences between sexes (34). For this purpose, many studies have been conducted in the veterinary medicine (8,20,37). No study was found on skull of Van cats in the literature reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The veterinary literature contains few descriptions of the cranial morphology in cats, with none being focused on the attachment of the tentorium ossium. [18][19][20] Although cats can be divided into three phenotypic skull shapes, round-shaped, triangular and cuneiform, the impact that parameters such as skull length, width and height have on the position of the Figure 4 The same post-acquisition processing was applied to the postoperative CT images of a 17-year-old cat. (a) As in the other cats, the line that demarks the tentorial attachment (red) and nuchal crest (green) is seen on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…The veterinary literature contains few descriptions of the cranial morphology in cats, with none being focused on the attachment of the tentorium ossium. 18–20 Although cats can be divided into three phenotypic skull shapes, round-shaped, triangular and cuneiform, the impact that parameters such as skull length, width and height have on the position of the tentorium ossium within the cranial cavity remains unknown. 19 In European cats, one external morphological feature that may be important is the squamous portion of the occipital bone, which approximates either the shape of an isosceles triangle or a semi-oval shape from a caudal viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a GWAS of joint angles from the horse shape space model applied to FM and Lipizzan horses revealed novel QTL for poll angle and elbow joint angle 12 . Two-dimensional (2D) geometric morphometric data have been already used to explore the genetic architecture of morphological differences in mollusks 13 , sorghum 14 , or house ies 15 , while three-dimensional (3D) data has been used to study facial traits in humans (summarized in 16 ), cats 17 and dogs 18 .…”
Section: Introductionmentioning
confidence: 99%